Informatic Competencies: the Genesis of the Concept - Valentyna Baranovska (Pedagogical Discourse, 2013)
On this basis of analysis of scientific publications we can see the essence of «informatic competencies» in the article. Singled out the main aspects of the interpretation of concepts such as «competencies», «competence», «professional competencies», «informatic competencies». Taking into account the results of research by the author, it was determined that informatic competencies of specialist must be looked as a system and first of all they appear in the process of their acquisition on all levels of improvement.